Não quero que gostem de mim, mas exijo que me respeitem : a prostituta cidadã, os significados e as ambiguidades na relação com o Ministério da Saúde - Rodrigues, Leina Peres (2014)
This ethnographic research was conducted at a non-governmental organization of civil society, NEP Núcleo de Estudos da Prostituição, which operates in the scope of the social movement of prostitutes in Porto Alegre and is part of the Rede Brasileira de Prostitutas. The interest of this research is to analyze how these women, who are part of prostitutes organizations, assume the identity of the social movement and how the relationship between these organizations and public policies is for this category. We address the discussion of prostitution in a broader way, within current policy issues. My goal was to analyze the relations of the organized social movement of prostitutes concerning public policies for preventing and coping with AIDS in Brazil, since ethnographic data show that the partnership between the Rede Brasileira de Prostitutas and the Ministry of Health is historical. I demonstrate that the health sector is now virtually the only form of sustainability of prostitutes organizations and is also the sector which at least seems willing to dialogue with this organized social movement that, despite the conflict of interests in this relationship, women who are part of this social movement build strategies to promote their demands and negotiate policy actions from this space.